Пам’яті Президента Національної Академії Наук України академіка Бориса Євгеновича Патона (Control systems & computers, 2020)
19 серпня 2020 р. на 102-му році пішов з життя Президент Національної академії наук України, двічі Герой Соціалістичної праці, перший Герой України академік Борис Євгенович Патон. Борис Євгенович був видатним українським вченим в галузі металургії, технології металів, електрозварювання та матеріалознавства, доктором технічних наук; Президентом НАН України з 1962 р., першим Героєм України; директором Інституту електрозварювання імені Євгена Патона НАН України; генеральним директором Міжгалузевого науково-технічного комплексу «Інститут електрозварювання імені Є.О. Патона»; президентом Міжнародної асоціації академій наук; членом Ради з питань науки та науково-технічної політики при Президентові України; головою Комітету з Державної премії України в галузі науки і техніки; членом Державної комісії з питань реформування, розвитку Збройних сил України, інших військових формувань, озброєння та військової техніки; першим заступником голови Національної ради зі сталого розвитку України. 19 августа 2020 на сто втором году скончался Президент Национальной академии наук Украины, дважды Герой Социалистического Труда, первый Герой Украины академик Борис Евгеньевич Патон. Борис Евгеньевич был выдающимся украинским ученым в области металлургии, технологии металлов, электросварки и материаловедения, доктором технических наук, Президентом Национальной академии наук Украины с 1962 г., первым Героем Украины; директором Института электросварки имени Евгения Патона НАН Украины; генеральным директором Межотраслевого научно-технического комплекса «Институт электросварки имени Е.О. Патона»; президентом Международной ассоциации академий наук; членом Совета по вопросам науки и научно-технической политики при Президенте Украины; председателем Комитета по Государственной премии Украины в области науки и техники; членом Государственной комиссии по вопросам реформирования, развития Вооруженных сил Украины, других военных формирований, вооружения и военной техники; первым заместителем председателя Национального совета по устойчивому развитию Украины On August 19, 2020, at the age of 102, the President of the National Academy of Sciences of Ukraine, twice Hero of Socialist Labor, the first Hero of Ukraine, academician Borys Yevhenovych Paton, died. Borys Paton was an outstanding Ukrainian scientist in the field of metallurgy, metal technology, electric welding and materials science, Doctor of Technical Sciences, President of the National Academy of Sciences of Ukraine (1962), the first Hero of Ukraine; Director of the Yevgen Paton Electric Welding Institute of the National Academy of Sciences of Ukraine; General Director of the Interbranch Scientific and Technical Complex “Institute of Electric Welding named after Ye.O.Paton “; President of the International Association of Academies of Sciences; member of the Council for Science and Scientific and Technical Policy under the President of Ukraine; Chairman of the Committee for the State Prize of Ukraine in Science and Technology; member of the State Commission on Reforming and Development of the Armed Forces of Ukraine, other military formations, weapons and military equipment; First Deputy Chairman of the National Council for Sustainable Development of Ukraine.